Kematian Ikan Kerapu Hibrida Cantik (Kerapu Macan >< Kerapu Batik) dan Cantang (Kerapu Macan >< Kerapu Kertang) di Keramba Jaring Apung di Teluk Kaping, Buleleng-Bali Akibat Infeksi Ektoparasit - Mahardika, Ketut; Mastuti, Indah; Sutarmat, Tatam (Jurnal Masyarakat Akuakultur Indonesia, 2019)
Several constraints in aquaculture are seasonal dependent especially for parasitic disease. Natural condition of aquatic environment are affecting pathogen and fish along season. This study observed parasitic infection causing mass mortality of hybrid grouper juveniles thruoghout the year. This study was conducted in floating net cage at Kaping Bay North Bali in 2016. The juveniles were stocked in May, July and August. Parasitic infection were observed in Juli-August. Two ectoparasite were found, they are gill worms (Pseudorhabdosynochus sp.) and sea leeches (Zeylanicobdella arugamensis). They caused appetite decreasing, swimming on the surface, dark body color, thiny body andt decreased the population about 44.9% - 47,53%. Gill worm infected the fish at the initial with intensity of 54-187 individu/gill, While sea leeches infected the fish later in August with intensity about 40-50 individu/fish. The record of water quality showed that temperature and salinity were increased in July. This conditions were coincide with seasonal change in 2016. This result suggested that seasonal change was unfavourable conditions for fish health moreover for stocking time.Â